Dietary fiber enhances milk yield in plateau dairy cows via activation of the rumen microbiota-mammary gland axis - Li, Bin; Wen, Dongxu; Zhou, Ziwei; Suolang, Quji; Siwang, Wangmu; Kangji, Lamu; Tang, Tuoxian; Liu, Zhenjiang; Wang, Yachun (Frontiers in Veterinary Science, 2025)
Milk yield in high-altitude regions such as the Qinghai-Tibet Plateau is low due to hypoxic stress and impaired mammary gland function. This study aims to determine whether a fiber-supplemented diet could increase milk yield in plateau dairy cows through modulating rumen microbiota and downstream metabolic signaling. Holstein cows were assigned to diets containing either Brassica rapa L. or an aquatic plant with a high neutral and acid-detergent fiber content. Milk yield and rumen metabolites were analyzed, and additional functional assays were performed using bovine mammary epithelial cells (BMECs) cultured under hypoxic conditions. The Brassica rapa L. supplementation significantly increased milk yield, which was associated with elevated levels of fiber-derived metabolites, including cholesterol valerate and 5-oxoeicosapentaenoic acid. These metabolites activated liver X receptor signaling in mammary cells under hypoxia, as validated by proteomic analysis and LXRα expression. Gene enrichment analysis revealed that LXR signaling was associated with lipid metabolism and cellular adaptation to low oxygen. These results support a fiber-microbiota-mammary axis, showing that fiber supplementation enhances milk yield through metabolic signaling. Moreover, this study presents a sustainable and feasible method to enhance milk production in ruminants under environmental stress.